Responsibility Of Doctors Who Perform Malpractices (An Overview Under Health Law) - Benny L H Hutahaean (Institute Of computer Science (IOCS), 2020)
The public's trust and positive assessments of the medical world are starting to decline, the medical world that used to seem unreachable by the law can now become a legal problem. This can be seen from the news that is reported by various mass media, both print and electronic media, there are often legal cases both civil and criminal which are examined by the Court related to medical practice or are often mentioned by many groups as: “Malpractice Medical